2021
DOI: 10.1007/s11033-020-06069-z
|View full text |Cite
|
Sign up to set email alerts
|

Role of MDA5 in regulating CXCL10 expression induced by TLR3 signaling in human rheumatoid fibroblast-like synoviocytes

Abstract: C-X-C motif chemokine 10 (CXCL10) is an inflammatory chemokine and a key molecule in the pathogenesis of rheumatoid arthritis (RA). Melanoma differentiation-associated gene 5 (MDA5) is an RNA helicase that plays a role in innate immune and inflammatory reactions. The details of the regulatory mechanisms of CXCL10 production and the precise role of MDA5 in RA synovitis have not been fully elucidated. The aim of this study was to examine the role of MDA5 in regulating CXCL10 expression in cultured human rheumato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Elevated levels of CCL3 are detected in the plasma of OA patients [ 39 ]; furthermore, overexpression of CCL3 and CCL4 has been detected in pro-inflammation-stimulated chondrocytes [ 40 ]. Other researchers have demonstrated chemokine expression from the (C-X-C motif) ligand (CXCL) family in rheumatoid fibroblast-like synoviocytes (CXCL6 [ 41 ]; CXCL10 [ 42 ]; CXCL11 [ 43 ]; CXCL16 [ 44 ]). Based on this result, we chose three of them (CXCL6, CXCL10, and CXCL16, which are also known as granulocyte chemotactic protein 2 (GCP-2), interferon gamma-induced protein 10 (IP-10), and phosphatidylserine and oxidized lipoprotein (SR-PSOX), respectively) whose expression was higher in HFLS-OAs than in HFLS after pro-inflammatory stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated levels of CCL3 are detected in the plasma of OA patients [ 39 ]; furthermore, overexpression of CCL3 and CCL4 has been detected in pro-inflammation-stimulated chondrocytes [ 40 ]. Other researchers have demonstrated chemokine expression from the (C-X-C motif) ligand (CXCL) family in rheumatoid fibroblast-like synoviocytes (CXCL6 [ 41 ]; CXCL10 [ 42 ]; CXCL11 [ 43 ]; CXCL16 [ 44 ]). Based on this result, we chose three of them (CXCL6, CXCL10, and CXCL16, which are also known as granulocyte chemotactic protein 2 (GCP-2), interferon gamma-induced protein 10 (IP-10), and phosphatidylserine and oxidized lipoprotein (SR-PSOX), respectively) whose expression was higher in HFLS-OAs than in HFLS after pro-inflammatory stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that CXCL10 plays an important role in the pathogenesis of RA and that it is important to clarify the mechanisms underlying the role of CXCL10 in RFLS. In RFLS treated with poly I:C, CXCL10 is produced via the TLR3/type I IFN/CXCL10 axis; a reaction that also involves MDA5 (another ISG) [10]. In this study, we found that ISG56 knockdown decreases the expression of CXCL10, but not MDA5.…”
Section: Experimental Biology and Medicinementioning
confidence: 47%
“…Published by Frontiers Society for Experimental Biology and Medicine study was approved by the Hirosaki University Graduate School of Medicine Ethics Committee (2018-1117) [10]. The sequences of siRNAs are as follows.…”
Section: Experimental Biology and Medicinementioning
confidence: 99%
See 1 more Smart Citation